2006
DOI: 10.1080/09687630600627066
|View full text |Cite
|
Sign up to set email alerts
|

Towards the prevention of alcohol abuse

Abstract: Mortality resulting from alcohol abuse in young French people is too high in spite of prevention campaigns for road safety in particular. There are problems in identifying alcohol abuse in young people in preventive medicine or alcohol care services. This study was carried out in alcohol centres; data from patients under 25 are analysed and compared to a same-age group of young adults who are consulting in preventive medicine centres. In comparison with older people, these two groups of young adults presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
1
0
2
Order By: Relevance
“…Men were more likely than women to be not only substance users but also abusers. These findings are in line with research suggesting that men compared to women are more likely to suffer from alcoholism or to abuse drugs (Facy & Rabaud, 2006). Several explanations have been proposed in terms of the greater availability and exposure to substances by men, higher tolerance due to their biological make-up, less normative constraints, etc.…”
Section: Gendersupporting
confidence: 89%
See 1 more Smart Citation
“…Men were more likely than women to be not only substance users but also abusers. These findings are in line with research suggesting that men compared to women are more likely to suffer from alcoholism or to abuse drugs (Facy & Rabaud, 2006). Several explanations have been proposed in terms of the greater availability and exposure to substances by men, higher tolerance due to their biological make-up, less normative constraints, etc.…”
Section: Gendersupporting
confidence: 89%
“…Cohort effects should also be carefully considered since there is evidence that they are present in substance use patterns, especially in countries that have undergone important sociopolitical upheavals (Facy & Rabaud, 2006;Holdcraft & Iacono, 2002) Considering the particular historical context and the age range of participants in the present study, it could be suggested that there might be important cohort effects to interpret. For instance, while 18 years old were born after the change of regime (i.e., in the 1990s), and grew up in the new democratic era, older participants have experienced at least partially the communist era, the transition state, and the democratic system.…”
Section: Agementioning
confidence: 97%
“…Por otro parte, más de la mitad de los encuestados consume durante los fines de semana cantidades que les llevan a emborracharse. Es decir, que se constata que no sólo ha aumentado el número de jóvenes que beben sino que se ha modificado el patrón de consumo, resultados coincidentes con numerosos trabajos, tanto de nuestro entorno más pró-ximo (Mateos, Páramo, Carrera y Rodríguez-López, 2002;Parker y Egginton, 2002;Observatorio Español sobre drogas, 2003, 2004, como del resto de Europa (Facy y Rabaud, 2006) y USA (Johnston, O'Malley y Bachman, 2006;Tucker, Orlando y Ellickson, 2003).…”
Section: Discussionunclassified
“…Este patrón de consumo de alcohol en segmentos cada vez más jóvenes de la población es frecuente no sólo en nuestro país (Bueno et al, 1995;Mirón, Serrano, Godás y Rodríguez, 1997;Ballester, Gil y Guirado, 2000;Gil y Ballester, 2002) sino también en otros países europeos como Francia (Facy y Rabaud, 2006) o Estados Unidos (Lewinshon, Rohde y Seeley, 1996; Johnson, Stiffman, Hadley-Ives y Elze, 2001;Johnston, O'Malley y Bachman, 2006). Se trata, por tanto, de un grave problema que afecta a una buena parte de la sociedad en su mayoría joven y de forma diferencial en función del género.…”
unclassified